UKRAINIAN AND GERMAN EXPERIENCE IN EDUCATING TROUBLED TEENAGERS AS A COMPONENT OF COMPARATIVE PROFESSIONAL PEDAGOGY (Comparative Professional Pedagogy, 2024)
The article analyzes the problem of educating troubled teenagers in Ukraine and Germany. Troubled teenagers need a personally oriented approach from teachers and the attention of parents and peers. Pedagogical and organizational components of troubled teenagers’ education in Ukraine and Germany are highlighted. It is substantiated that there are many common features in educational work with difficult-to-educate teenagers in Ukraine and Germany.Troubled teenagers are characterized as adolescents who are physically and mentally healthy, although consciously or unconsciously resist purposeful pedagogical influence, characterized by defects in personality development (lack of moral and volitional qualities, problems with accepting value orientations) as well as violations of norms accepted in society and rules of behavior, which complicates their formation as individuals, that is, their socialization.The purpose of the article is to theoretically analyze the pedagogical and organizational components of modern education of troubled teenagers in Ukraine and Germany.Having analyzed the works of scientists who studied the problem of educational work with troubled teenagers in Ukraine and Germany, it can be stated that today there are common directions in the education of this category of teenagers. Both in Ukraine and in Germany, there are groups of teenagers with difficult upbringing who experience stressful situations in communication, trouble at school, insecurity and behavioral deviations. This category of teenagers needs professional round-the-clock free help from specialists in the pedagogical and social spheres. Their upbringing is carried out both during the educational process and in extracurricular time, both in Ukraine and in Germany. An important direction of educational work with troubled teenagers is the individual pedagogical support of specialists from non-profit foundations and institutes that practice the use of experimental pedagogical and therapeutic methods. The theoretical basis of this direction of educational work needs to be refined from pedagogical, social and material perspectives.
Keywords: upbringing; educational work; troubled teenagers; education of troubled teenagers in Ukraine; education of troubled teenagers in Germany